Incidence of food anaphylaxis in people with food allergy: a systematic review and meta‐analysis. Issue 11 (15th October 2015) - Umasunthar, T.; Leonardi‐Bee, J.; Turner, P. J.; Hodes, M.; Gore, C.; Warner, J. O.; Boyle, R. J.
Summary Background Food allergy is a common cause of anaphylaxis, but the incidence of anaphylaxis in food allergic people is unknown. Methods We undertook a systematic review and meta‐analysis, using the inverse variance method. Two authors selected studies by consensus, independently extracted data and assessed study quality using the Newcastle–Ottawa assessment scale. We searched Medline, Embase, PsychInfo, CINAHL, Web of Science, LILACS and AMED between January 1946 and September 2012 and recent conference abstracts. We included registries, databases or cohort studies which described the number of food anaphylaxis cases in a defined population and time period and applied an assumed population prevalence of food allergy. Results We included data from 34 studies. There was high heterogeneity between study results, possibly due to variation in study populations, anaphylaxis definition and data collection methods. In food allergic people, medically coded food anaphylaxis had an incidence rate of 0.14 per 100 person‐years (95% CI 0.05, 0.35; range 0.01, 1.28). In sensitivity analysis using different estimated food allergy prevalence, the incidence varied from 0.11 to 0.21 per 100 person‐years. At age 0–19, the incidence rate for anaphylaxis in food allergic people was 0.20 (95% CI 0.09, 0.43; range 0.01, 2.55; sensitivity analysis 0.08, 0.39). At age 0–4, an incidence rate of up to 7.00 per 100 person‐years has been reported. In food allergic people, hospital admission due to food anaphylaxis had an incidence rate of 0.09 (95% CI 0.01, 0.67; range 0.02, 0.81) per 1000 person‐years; 0.20 (95% CI 0.10, 0.43; range 0.04, 2.25) at age 0–19 and 0.50 (0.26, 0.93; range 0.08, 2.82) at age 0–4. Conclusion In food allergic people, the incidence of food allergic reactions which are coded as anaphylaxis by healthcare systems is low at all ages, but appears to be highest in young children.